Development and testing of an efficient and cost-effective underwater propulsion system. (November 2019) - Paolucci, Libero; Grasso, Emanuele; Grasso, Francesco; König, Niklas; Pagliai, Marco; Ridolfi, Alessandro; Rindi, Andrea; Allotta, Benedetto
Underwater vehicle propulsion performed by exploiting electrical motor is in general the most flexible solution and it is growing in popularity because of its high efficiency both at high and at low advance speed, quick and simple deployment, low costs, and encumbrance. In the present work, permanent magnet synchronous motors for underwater propulsion are proposed. In particular, advanced sensorless control techniques of permanent magnet synchronous motors permit reduced costs, high reliability, and performances. When dealing with small autonomous underwater vehicle propulsion, such devices are hard to find in the market. Hence, the authors focused the research in the development of a system able to perform a reliable rotational speed and torque sensorless estimation. The design and implementation of a complete solution for underwater propulsion are presented as well as a novel rotor polarity identification technique exploiting a high-frequency injection control. Pool tests for the identification of the performances and of the dynamic parameters of the propulsion system are presented. Finally, the possibility of operating a sensorless estimation of the thrust and torque exerted by the propeller and pool test measurements are presented. These features could be exploited to improve navigation accuracy and involves obvious benefits in terms of cost reduction and reliability of the system.